2015
DOI: 10.1108/ijebr-12-2013-0218
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and the SME sector

Abstract: Structured Abstract: PurposeAlthough foreign direct investment (FDI) and entrepreneurship are potential routes to recovery (Girma and Wakelin, 2001; Lyon et al., 2002), existing literature is divided on the relationship between the two. This study examines the influence of foreign investment on the local SME sector after the 2008 financial crisis. Design/methodology/approachLocal authority district data from Great Britain is used to examine the influence of foreign firm employment on the size of the local SME … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Instead, a wide range of different measures have been used including, the number of projects (Dimitropoulou, McCann, & Burke, ), and the proportion of employment in foreign firms (Thompson & Zang, , , ). Here the focus is on the opportunity to cooperate with foreign firms in order to innovate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, a wide range of different measures have been used including, the number of projects (Dimitropoulou, McCann, & Burke, ), and the proportion of employment in foreign firms (Thompson & Zang, , , ). Here the focus is on the opportunity to cooperate with foreign firms in order to innovate.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are potential benefits from greater foreign influence in the local economy through technology and management spillovers (Fu, ) and increased demand for domestic production (Markusen & Venables, ), there are also potential negatives through competition in either the output or input markets (Girma, Greenaway, & Wakelin, ; Martins, ) and by attracting the most entrepreneurial individuals away from business ownership into corporate employment (Grossman, ). It is therefore understandable that empirical studies examining the relationship between foreign influence and entrepreneurship find a range of results (Ke, ; Liu, ; Thompson & Zang, , ).…”
Section: Introductionmentioning
confidence: 99%
“…We also control for cumulative state-owned enterprises (SOE) and foreign direct investment (FDI) capital, which represent the level of competitiveness of the local market. The literature has shown that the presence of foreign or state-owned enterprises could pose a severe threat to the performance of private small businesses (Thompson & Wenyu, 2015).…”
Section: Control Variablesmentioning
confidence: 99%
“…Firm performance has been defined as; how a firm uses its resources to sustain in the marketplace (Thompson & Zang, 2015), achievement of growth and strategic goals (Hult, Hurley, & Knight, 2004). Firm performance can be further defined as the relationship between the actions taken together with competitive forces, which allow the firm to use the internal resources to adjust to the external environment, incorporating the ideas of effectiveness and efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%